Phenotypic variant forms of Trichomonas vaginalis trophozoites from cervical neoplasia patients - Yusof, A.M.; Kumar, S. (2012)
The protozoan Trichomonas vaginalis a sexually transmitted protozoan parasite causes vaginitis, urethritis and cervicitis in humans. The present study highlights phenotypic variant forms of trophozoites isolated from patients suffering from cervical neoplasia condition. The growth curve of 10 isolates i.e., four non-cervical neoplasia (NCN) isolates (NCN1 NCN4) and six cervical neoplasia (CN) isolates (CN1CN6) showed two distinct and different in vitro growth profiles. The parasite count and growth rates were significantly higher in trophozoites from CN isolates in cultures of day 2 up to day 8 (p < 0.05, MannâWhitney test). The average generation time was 1.84 Â± 0.40 and 3.38 Â± 0.55 h for NCN and CN isolates respectively. The nucleus of trophozoites in CN isolates using acridine orange and DAPI showed more intense staining revealing higher nuclear content. The FITC-labeled Concanavalin A stained stronger green fluorescence with surface of trophozoites in CN isolates showing more rough and creased surface with numerous deep micropores. Transmission electron microscopy studies revealed that there was higher numbers of vacuoles and hydrogenosomes in these forms. The study mounted staining techniques, growth profiles, morphology, morphometry studies using scanning and transmission electron microscopy and confirms that the trophozoites from cervical neoplasia proliferates at a higher rate, shows higher FITC-labeled Concanavalin A binding with rough and creased surface implying that these are virulent forms which can aggravate or exacerbate cervical neoplasia conditions. The large numbers of hyrogenosomes and vacuoles implies that these forms are active and implicates a possible role in such conditions.